Time-dependent alterations in the rat nigrostriatal system after intrastriatal injection of fibrils formed by α–Syn and tau fragments - Yang, Xiaoman; Wang, Jialing; Zeng, Weiqi; Zhang, Xiaoqian; Yang, Xiaomei; Xu, Yu; Xu, Yan; Cao, Xuebing (Frontiers in Aging Neuroscience, 2022)
Accurate demonstration of phosphorylated α-synuclein aggregation and propagation, progressive nigrostriatal degeneration and motor deficits will help further research on elucidating the mechanisms of Parkinson’s Disease. α-synucleinN103 and tauN368, cleaved by activated asparagine endopeptidase in Parkinson’s Disease, robustly interacted with each other and triggered endogenous α-synuclein accumulation in a strong manner. However, the detailed pathophysiological process caused by the complex remains to be established. In this study, rats were unilaterally inoculated with 15 or 30 μg of this complex or vehicle (phosphate buffered saline, PBS). Over a 6-month period post injection, we then investigated the abundance of pSyn inclusions, nigrostriatal degeneration, and changes in axonal transport proteins to identify the various dynamic pathological changes caused by pSyn aggregates in the nigrostriatal system. As expected, rats displayed a dose-dependent increase in the amount of α-synuclein inclusions, and progressive dopaminergic neurodegeneration was observed throughout the study, reaching 30% at 6 months post injection. Impairments in anterograde axonal transport, followed by retrograde transport, were observed prior to neuron death, which was first discovered in the PFFs model. The current results demonstrate the value of a novel rat model of Parkinson’s disease characterized by widespread, “seed”-initiated endogenous α-Syn pathology, impaired axonal transport, and a neurodegenerative cascade in the nigrostriatal system. Notably, the present study is the first to examine alterations in axonal transport proteins in a PFF model, providing an appropriate foundation for future research regarding the mechanisms leading to subsequent neurodegeneration. As this model recapitulates some essential features of Parkinson’s disease, it provides an important platform for further research on specific pathogenic mechanisms and pre-clinical evaluations of novel therapeutic strategies.